Defining an Intraoperative Hypotension Threshold in Association with De Novo Renal Replacement Therapy after Cardiac Surgery. (June 2020) - Ngu, Janet M. C.; Jabagi, Habib; Chung, Amy M.; Boodhwani, Munir; Ruel, Marc; Bourke, Michael; Sun, Louise Y.
Abstract : Background: Acute kidney injury (AKI) is a frequent and deadly complication after cardiac surgery. In the absence of effective therapies, a focus on risk factor identification and modification has been the mainstay of management. The authors sought to determine the impact of intraoperative hypotension on de novo postoperative renal replacement therapy in patients undergoing cardiac surgery, hypothesizing that prolonged periods of hypotension during and after cardiopulmonary bypass (CPB) were associated with an increased risk of renal replacement therapy. Methods: Included in this single-center retrospective cohort study were adult patients who underwent cardiac surgery requiring CPB between November 2009 and April 2015. Excluded were patients who were dialysis dependent, underwent thoracic aorta or off-pump procedures, or died before receiving renal replacement therapy. Degrees of hypotension were defined by mean arterial pressure (MAP) as less than 55, 55 to 64, and 65 to 74 mmHg before, during, and after CPB. The primary outcome was de novo renal replacement therapy. Results: Of 6, 523 patient records, 336 (5.2%) required new postoperative renal replacement therapy. Each 10-min epoch of MAP less than 55 mmHg post-CPB was associated with an adjusted odds ratio of 1.13 (95% CI, 1.05 to 1.23; P = 0.002), and each 10-min epoch of MAP between 55 and 64 mmHg post-CPB was associated with an adjusted odds ratio of 1.12 (95% CI, 1.06 to 1.18; P = 0.0001) for renal replacement therapy. The authors did not observe an association between hypotension before and during CPB with renal replacement therapy. Conclusions: MAP less than 65 mmHg for 10 min or more post-CPB is associated with an increased risk of de novo postoperative renal replacement therapy. The association between intraoperative hypotension and AKI was weaker in comparison to factors such as renal insufficiency, heart failure, obesity, anemia, complex or emergent surgery, and new-onset postoperative atrial fibrillation. Nonetheless, post-CPB hypotension is a potentially easier modifiable risk factor that warrants further investigation. Abstract : Varying definitions of hypotension before and during cardiopulmonary bypass are not associated with renal replacement therapy. Mean arterial pressure less than 55 or between 55 and 64 mmHg for 10 or more minutes after cardiopulmonary bypass is associated with renal replacement therapy. The association of post–cardiopulmonary bypass hypotension with renal replacement therapy is weaker than nonmodifiable procedure and patient risk factors.Supplemental Digital Content is available in the text.